Pc 5 ミャクドウ ヲ モチイタ チジキ キョウヤク テン ノ スイテイ - 加藤, 賢一; カトウ, ケンイチ; 利根川, 豊; トネガワ, ユタカ; 佐藤, 夏雄; サトウ, ナツオ; Kato, Ken-ichi; Tonegawa, Yutaka; Sato, Natsuo (1992)
P(論文) 本論文では, 地磁気脈動の特性と観測点間の位相差を利用したTONEGAWA and SATOの方法を用いて, アイスランド3観測点と南極3観測点で1988年3月と5月に同時観測された午前側のPc5脈動から地磁気共役点の推定を試みた。その際, Pc5地磁気脈動の特性を奇数次モードの定在波であり, そして水平面での位相変化は線形であると仮定した。このような方法を用いた結果, Pc5脈動から求めた地磁気共役点とTSYGANENKOの地球磁場モデルから求めた地磁気共役点はよい一致を示した。その範囲は経度方向±3°, これは1/5波長以下, また緯度方向は±0.5°内に位置している。 In the present paper, we have attempted to estimate the geomagnetic conjugate points by the method of TONEGAWA and SATO using Pc5 geomagnetic pulsation data obtained simultaneously at three stations in Iceland and at three stations in Antarctica (including Syowa Station) during the period of March and May in 1988. It is assumed in the estimation that Pc5 pulsations are odd mode standing oscillations of the field line and have linear phase variations among the stations in the horizontal plane. The result shows that conjugate points of Syowa Station estimated from Pc5 events are concentrated around the point calculated from the magnetic field model of TSYGANENKO, within the range of ±3°in the longitude, i. e., less than 1/5 wave length, and ±0.5°in the latitude. departmental bulletin paper